EP.TH.893Virtual Clinic follow-up in Laparoscopic Fundoplication Surgery. (28th October 2021) - Ji, Chenchen; Mitchell, Benjamin; Tan, Christine; Toh, Simon
Abstract: Aims: There are clinical and financial incentives to reduce follow-up NHS clinics after elective surgery. 55% of our laparoscopic anti-reflux procedures are day-cases procedures. To reduce consultant clinic workload and unnecessary face-to-face patient reviews, we introduced a laparoscopic surgical care practitioner (LSCP) based Virtual Clinic. Methods: Patients were telephoned on day 1 and 5 to ensure they were managing their diet without significant post-operative symptoms. This was followed by a Virtual Clinic follow-up at 6-8 weeks, using a universal list of questions and template, and an electronic letter with outcomes recorded. 149 patients underwent laparoscopic fundoplication surgery from September 2016 – May 2018. All follow-up clinics, both virtual and face-to-face, were recorded electronically. These were reviewed, data collected and analysed. Results: Between September 2016 – May 2018, 149 patients had laparoscopic fundoplication surgery at our trust with the following clinic outcomes: Conclusions: Our LSCP Virtual Clinics discharged 50 out of 149 (33%) patients with no need for face-to-face clinic time, and no detriment to patient care. Those requiring further follow-up were patients who had difficulty managing dietary changes, or experiencing symptoms like dysphagia, often needing physical review and further investigations. Furthermore, patients have expressed high satisfaction with this service. Virtual clinic follow-up is safe, patient-friendly, and reduces both clinical and financial load on NHS outpatient clinics.